Sistem Perdagangan Kerajaan Samudera-Pasai - Arifin, Abdul Hadi (PASAI, 2013)
Future trading system of the Kingdom Samudera-Pasai, is believed to have used deureuham of gold coins, which is the first currency Aceh. As the maritime nation where the economy relies on trade and shipping, to each foreign ship transporting the goods entered in port on the wear for taxed. Reviewed in terms of geographical and socio-economic, samudera-pasai kingdom indeed a significant highly important region as liaison between the centers of trade in the Archipelago, India, China, Arab, and European and has a sufficient good harbor at the time. Exports and imports also become developed and opened international trading network. Goods for commercial purpose and the export is gold, rice, pepper, silk, benzoin and kamphon, with a trading system that has been forward and complicated. Silk, gold balls and is an important commodity in world trade. Gold and balls is a product favored by the population in various countries in Africa and Europe. While silk is product favored by almost all nations. This silk trade route later became a very important pathway, not only economically as selling a product that has a high and rising demand in Asia, but this pathway is also used as a network to proselytizing Islam.